2021
DOI: 10.1111/sum.12738
|View full text |Cite
|
Sign up to set email alerts
|

Do different agronomic soil tests identify similar nutrient deficiencies?

Abstract: Farmers and crop advisors rely on soil testing to evaluate soil nutrient status and to plan fertilizer applications. Plants require at least 14 essential plant nutrients, which can be classified into macro-(N, P, K, S, Ca, Mg and Na) and micronutrients (Cu, Zn, Mn, B, Mo, Si, Ni, and Cl) (Kirkby, 2012). Several different soil testing methods have been developed to estimate the capability of soil to provide nutrients for crops, without clear consensus on which method to apply (Hochmuth & Hanlon, 2010;Stockdale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The above results should be interpreted after taking into consideration that the measurement protocol, the Haney test, is still undergoing field evaluation and refinement in contrasting soils and climates across the United States. However, multiple recent reports support the usefulness of this test to characterize soil health (Ansley et al, 2021;Bavougian et al, 2019;Mattila & Rajala, 2022). Bavougian et al (2019) reported the appropriateness of the Haney soil health test for quantifying the effects of a change in management such as cover cropping to replace fallow periods in annual systems.…”
Section: Discussionmentioning
confidence: 99%
“…The above results should be interpreted after taking into consideration that the measurement protocol, the Haney test, is still undergoing field evaluation and refinement in contrasting soils and climates across the United States. However, multiple recent reports support the usefulness of this test to characterize soil health (Ansley et al, 2021;Bavougian et al, 2019;Mattila & Rajala, 2022). Bavougian et al (2019) reported the appropriateness of the Haney soil health test for quantifying the effects of a change in management such as cover cropping to replace fallow periods in annual systems.…”
Section: Discussionmentioning
confidence: 99%
“…However, neither the total nor Mehlich extractable soil concentrations are a true measure of the availability of a nutrient to a plant. Total concentrations include all of the nutrients strongly sorbed to organic or mineral components of the soil that might only be available over long timescales [ 34 ], whereas the Mehlich extractant is a better proxy for availability but cannot possibly replicate the intricacies of soil chemistry and plant and microorganism biology that combine to make nutrients available to plants [ 35 ]. Furthermore, Mechlich extraction uses an acidic extractant, and therefore may not have had an equal effect on the AH and AL soils.…”
Section: Discussionmentioning
confidence: 99%
“…maintain target ranges of plant available nutrients in soil (phosphorus (P), potassium (K) and magnesium (Mg) specifically; Steinfurth et al, 2022;Mattila & Rajala, 2022;Zbíral, 2016). It has been recognised for many years that there are a number of different soil test methods available.…”
Section: Highlightsmentioning
confidence: 99%
“…Fertiliser recommendations and advice to farmers are primarily based on agronomic requirements, specific to soil and crop type and generated individually within each country. The general common principle is to reach or maintain target ranges of plant available nutrients in soil (phosphorus (P), potassium (K) and magnesium (Mg) specifically; Steinfurth et al, 2022; Mattila & Rajala, 2022; Zbíral, 2016). It has been recognised for many years that there are a number of different soil test methods available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation